A stochastic programming approach for floods emergency logistics - Garrido, Rodrigo A.; Lamas, Patricio; Pino, Francisco J. (Transportation research. Part E, Logistics and transportation review, 2015)
•A stochastic optimization model for floods events with unsatisfied demand is designed.•Stochastic demand for emergency supplies is incorporated and must be satisfied to a level of service.•Flood events are simulated through a stochastic process with spatio-temporal correlations.•Objective combines distribution time and cost. Solution is found by sample average approximation. This article presents a model to assist decision makers in the logistics of a flood emergency. The model attempts to optimize inventory levels for emergency supplies as well as vehicles’ availability, in order to deliver enough supplies to satisfy demands with a given probability. A spatio-temporal stochastic process represents the flood occurrence. The model is approximately solved with sample average approximation. The article presents a method to quantify the impact of the various intervening logistics parameters. An example is provided and a sensitivity analysis is performed. The studied example shows large differences between the impacts of logistics parameters such as number of products, number of periods, inventory capacity and degree of demand fulfillment on the logistics cost and time. This methodology emerges as a valuable tool to help decision makers to allocate resources both before and after a flood occurs, with the aim of minimizing the undesirable effects of such events.